Habitat fragmentation induces rapid divergence of migratory and isolated sticklebacks. (23rd November 2021) - Ramesh, Aparajitha; Groothuis, Ton G G; Weissing, Franz J; Nicolaus, Marion
Abstract: The adaptive capacity of many organisms is seriously challenged by human-imposed environmental change, which currently happens at unprecedented rates and magnitudes. For migratory fish, habitat fragmentation is a major challenge that can compromise their survival and reproduction. Therefore, it is important to study if fish populations can adapt to such modifications of their habitat. Here, we study whether originally anadromous three-spined stickleback populations ( Gasterosteus aculeatus; " migrants") changed in behavior and morphology in response to human-induced isolation. We made use of a natural field-experiment, where the construction of pumping stations and sluices in the 1970s unintendedly created replicates of land-locked stickleback populations ("resident") in the Netherlands. For two years, we systematically tested populations of residents and migrants for differences in morphology and behavioral traits (activity, aggressiveness, exploration, boldness, and shoaling) in lab-based assays. We detected differences between migrant and resident populations in virtually all phenotypic traits studied: compared with the ancestral migrants, residents were smaller in size, had fewer and smaller plates and were significantly more active, aggressive, exploratory and bolder, and shoaled less. Despite large ecological differences between 2018 and 2019, results were largely consistent across the two years. Our study shows that human-induced environmental change has led to the rapid and consistent morphological and behavioral divergence of stickleback populations in about 50 generations. Such changes may be adaptive but this remains to be tested. Abstract : The adaptive capacity of many organisms is seriously challenged by human-imposed environmental changes. For example, migratory fish encounter man-made barriers that impede their movements and force them to adopt a resident lifecycle. Here, we study whether and how populations of three-spined sticklebacks diverged in response to human-induced isolation. We show that about 50 generations of isolation were sufficient to induce substantial morphological and behavioral differentiation between land-locked populations ("residents") and their migratory ancestors ("migrants").